The Influence of Arabic Gum on the Quality of Instant Ginger (Zingiber officinale Roscoe) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Instant ginger was traditionally made by crystallizing ginger extract and sugar. The product was easily reconstituted into ginger beverage by dissolution in warm water. The atsiries on this beverage would refresh and warming the body. Unfortunately, the atsiries are unstable during storage. The research is aimed to study the influence of arabic gum on the stability of the product. The method being used was complete random de .. sign with two replications. The concentration of the arabic gum was 0, 0.02, 0.04, 0.06 and 0.08%. The parameter being analyzed were moisture content, ash content, total soluble solute, viscosity, and sensory (aroma, color, viscosity, solubility and taste). The result showed that addition ofArabic gum would influence all of the parameters except solubility, color and taste. The best formula was obtained by the addition of 0.04% Arabic gum with the following criteria: ginger strong â ginger stronger aroma, yellowish brown color, slightly viscous, slightly soluble, sweet and slightly warm taste, moisture content 4. SS%, ash content 3.95%, total soluble solute 49.43%and viscosity 21.70 cps. For all criteria the preferences are like moderately. Keywords: instant ginger, arabic gum INTRODUCTION Ginger is one of plants that many useful in Indonesia. It uses as spices, sweets, pickles, or traditional medicine, beside as a flavoring agent in perfumed or medicine product. It can give many effeCts, if used in oral like feeling fresh and warm the bodies. Beside that, ginger can prevent and cure various health disorder including common cold, cough, diarrhea (Duke, 2003), anti tumor, anticancer (Craig, 1999), anti fungal, antibacterial (Sutarno, et al., 1999), and increase immunity if it is used as a beverage (Zakaria, et al., 1999). Because it contains active ingredients like gingerol, zingiberene, zingiberol, ginger oil, oleoresin and others that are atsiries oil. One of a beverage that can be made by ginger is instant ginger. Instant ginger is traditionally made by crystallizing ginger extract and sugar. The product is easily reconstituted into ginger beverage by dissolution in warm water. The actives ingredients especially atsiries oil is a volatile compound that are unstable during storage. To hold it the researcher try to added Arabic gum in instant. ginger. The research is aimed to study the influence of arabic gum on the stability of the product.